Security Mechanisms in Wireless Sensor Networks (WSNs) (International Journal of Food and Nutritional Sciences, 2022)
Wireless Sensor Networks (WSNs) have emerged as a critical technology in various domains, facilitating real-time data collection and monitoring. However, their widespread adoption is hindered by inherent security vulnerabilities that expose them to various threats. This paper delves into the imperative task of fortifying WSNs through the implementation of robust security mechanisms. The study evaluates encryption and authentication protocols, key management strategies, intrusion detection systems, and secure routing algorithms tailored for resource-constrained sensor nodes. Through comprehensive simulations and case studies, the research demonstrates the efficacy of the proposed security measures in safeguarding WSN communications and data integrity. The findings underscore the pivotal role of security in enabling the seamless operation and reliability of WSN applications, offering a solid foundation for future advancements in this critical field.